(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
In this study, the specific activity was measured for samples of agricultural crops in AlMishkhab district of Al-Najaf governorate. Ten different samples of these crops were collected. To determine the specific activity of each of the radionuclides (40K, 232Th, 238U(226Ra), The sodium iodide detector system activated with thallium "3" × 3 NaI (Tl) was used. ) to (9.991) Bq/kg at a rate of (5.2447) Bq/kg. As for the specific activity of 232Th, it ranged from (0.796) Bq/kg to (4.298) Bq/kg with a rate of (2.3696) Bq/kg. As for 40K, the specific activity ranged from (47.805) Bq/kg to (190.104) Bq/kg with a rate of (123.213) Bq/kg This variation in the specific effectiveness values is less than the values set by the United Nations Atomic Energy Commission (UNCEAR), and this committee has given fixed quantities allowed for the values of these indicators in order for the consumed samples to be safe from radiation risks. The radium equivalent (Raeq) changes from (8.2789) Bq/kg to (35.1523) Bq/kg at a rate of (19.86122) Bq/kg. It was found that the internal risk level (Hin) changes from (0.0284) to (0.1219) at a rate of (0.070425. The total average effective dose associated with exposure as a result of ingesting radionuclides was calculated in the samples of the current study, and all the results of the specific activity rate and risk coefficients for 238U (226Ra), 232Th, and 40K were compared with the limits recommended by UNCEAR, and it was found to be below those values